Neuroscience in Linguistic Patterns of Communication Campaigns for Environmental Sustainability - Saczyna, Magdalena (Problemy Ekorozwoju, 2019)
Neuroscience is the scientific study of the nervous system and the brain, with the aim to unravel their function. Although the importance of this discipline in the social sciences has been widely discussed, there are no studies that use this potential for environmental sustainability-related applications. To the author knowledge investigations on environmental problems communication from the linguistic perspective in the context of neuroscience have been scarcely examined. The purpose of this article is to shed light on this gap, indicate the potential of neuroscience in communication campaigns, and highlight the role of linguistics elements as factors enforcing change in human proenvironmental behavior. The author hypostatizes that the future of sustainability efforts must increasingly be seen in a systemic and holistic way and neuroscience should be seen as an alternative remedy for environmental problems. Moreover, the author examines a potential of neuroscience based on linguistic model of communication that could facilitate behavior change in the context of environmental problems and sheds light on relationship between two disciplines: linguistics and the field that investigates unconscious variables that determine human’s behavior – neuroscience. This article is a call for action to incorporate findings made in the field of neuroscience in mass communication message design to promote environmental sustainability more effective.